Summary of the African Leaders Nairobi Declaration on Climate Change and Call to Action - African Union Commission (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The African Heads of State and Government gathered for the inaugural Africa Climate Summit in Nairobi, Kenya, from 4th to 6th September 2023. The African Leaders Nairobi Declaration is a key outcome of the Africa Climate Summit.